Dynamic polarity of curved aromatic soot precursors - Martin, Jacob W. (2020)
In this paper, we answer the question of whether polar curved aromatics are persistently polar at flame temperatures. We find, using electronic structure calculations and transition state theory, that the inversion barriers of curved aromatics (cPAH) 0.9–1.2 nm in diameter are high and that they are not able to invert over the timescales and at the high temperatures found in sooting flames. We find a transition for smaller curved aromatics between 11–15 ( ≈  0.8 nm) rings where the increasing strain introduced from the pentagonal ring increases the inversion barrier leading to rigidity. We then performed ab initio quantum molecular dynamics to find the molecular dipole fluctuations of a nanometre sized cPAH at 1500 K. We found the bending mode of the bowl shaped molecule gave rise to the largest fluctuations on the dipole moment by  ± 0.5–1 debye about the equilibrium value of 5.00 debye, indicating persistent polarity. We also observed binding of a chemi-ion at 1500 K over 2 ps, suggesting the molecular dipole of cPAH will be an important consideration in soot formation mechanisms.